Learner perceptions of family‐centred rounds. (10th February 2020) - Goodrich, Nathaniel; Naslund, Rachel; Bossert, Whitney; Johnson, Stephanie; Salcedo, Stacy; Lyden, Liz; Dallaghan, Gary Beck
Summary: Background: Family‐centred rounds (FCRs) are common in paediatric inpatient medicine. FCRs lead to shorter hospital stays, improved communication, and improved patient and family satisfaction. Rounding structures can differ between institutions based on participants, the location of rounds and the role of trainees. The aim of our study was to compare walking hallway rounds with a new conference‐room rounding style, as measured by learner perceptions of FCRs. Methods: All students participating in FCRs on two hospitalist teams were included in this study. In October 2017, a family‐centred conference‐room rounding model was developed. Team A adopted conference‐room rounds whereas team B continued to use hallway rounds. Student and resident evaluations were constructed using a nine‐point Likert scale (1, strongly disagree; 9, strongly agree). Evaluations assessed various perceived components of rounding. Results: There were statistically significant differences between the evaluation responses from student team A ( n  = 21) versus student team B ( n  = 32) regarding perceived comfort in presenting (A = 7.86, B = 6.56, t  = 3.42, p ≤ 0.001), confidence talking to families about medical decision making (A = 7.19, B = 6.32, t  = 2.57, p  = 0.013), educational value of rounds (A = 8.05, B = 6.16, z  = –4.39, p ≤ 0.0001), value as a team member (A = 7.38, B = 6.34, z  = –2.22, p = 0.013) and preparedness to round (A = 7.76, B = 6.34, z  = –3.67, p ≤ 0.0001). Among residents, there were statistically significant differences regarding the perceived efficiency of rounds (A = 6.69, B = 4.89, t  = 2.09, p = 0.048) and family engagement (A = 7.81, B = 5.89, z  = –2.67, p = 0.003). Discussion: Compared with hallway rounds, students and residents had improved learner perceptions of FCRs when participating in conference‐room rounds. Some component of conference room rounding may be beneficial to learners while maintaining family‐centered care.